Peran Kepala Sekolah Sebagai Manajer (Studi Multisitus) Di MIN 1 Dan MIN 2 Flores Timur - Ilmin Sakir; Akhsanul In’am; Sri Hartiningsih (Jurnal Kebijakan dan Pengembangan Pendidikan, 2018)
Abstract: This study aims to examine the role of the MIN 1 and MIN 2 principals of East Flores as managers, success supporting factors, the obstacles faced and the principal's efforts to overcome obstacles. The research method used is a qualitative approach with the type of research is descriptive. This research uses a multi-site study. Data obtained through interviews, observation, and study documentation. The results of this study indicate that the roles of the heads of MIN 1 and MIN 2 as managers are 1) Involving teachers and staff in managing school programs; 2) Conduct curriculum management; 3) Creating a conducive learning and achievement climate; 4) Include teachers in training to improve their competence; 5) Facilitating facilities and infrastructure supporting school activities; 6) Planning a budget; 7) Conduct student management activities; 8) Specifically assigning teachers to oversee the program, and 9) Conduct supervision. Internal factors that support the success of the heads of MIN 1 and MIN 2 East Flores as managers are the togetherness of the teachers to optimize their potential and the willingness to sincerely carry out the school programs that have been planned together. The external factor is the strong support of student guardians in the programs that have been run by schools. The internal obstacle faced by the heads of MIN 1 and MIN 2 East Flores as managers are the limited time for teachers to carry out or run the program to the maximum extent possible. The external obstacle is the student's guardian awareness of the school program. Efforts made by the heads of MIN 1 and MIN 2 East Flores as managers in improving the quality of schools to overcome internal and external problems are communicating to teachers to be more active in carrying out or carrying out planned programs.Keywords: Principal, Manager, Multisitus Study Abstrak: Penelitian ini bertujuan untuk mengkaji peran kepala sekolah MIN 1 dan MIN 2 Flores Timur sebagai manajer, faktor pendukung keberhasilan, kendala yang dihadapi dan upaya kepala sekolah mengatasi kendala. Metode penelitian yang dilakukan adalah pendekatan kualitatif dengan jenis penelitian adalah deskriptif. Penelitian ini menggunakan studi multisitus. Data diperoleh melalui wawancara, observasi, dan studi dokumentasi. Hasil penelitian ini menunjukan bahwa peran kepala MIN 1 dan MIN 2 sebagai manajer yaitu 1) Melibatkan guru dan pegawai dalam pengelolaan program sekolah; 2) Melakukan pengelolaan kurikulum; 3) Mewujudkan iklim belajar dan berprestasi yang kondusif; 4) Mengikutkan guru-guru dalam pelatihan untuk meningkatkan kompetensinya; 5) Memfasilitasi sarana dan prasarana pendukung kegiatan sekolah; 6) Merencanakan penganggaran; 7) Melakukan kegiatan pengelolaan kesiswaan; 8) Menugaskan secara khusus guru-guru untuk mengawal program, dan 9) Melakukan pengawasan. Faktor internal yang menjadi pendukung keberhasilan kepala MIN 1 dan MIN 2 Flores Timur sebagai manajer adalah kebersamaan guru-guru untuk mengoptimalkan potensi yang dimiliki dan keinginnan yang ikhlas untuk mejalankan program sekolah yang telah direncankan bersama-sama. Faktor eksternalnya adalah dukungan wali murid yang kuat pada program yang telah dijalankan oleh sekolah. Kendala internal yang dihadapi kepala MIN 1 dan MIN 2 Flores Timur sebagai manajer adalah keterbatasan waktu dari guru-guru untuk melakukan atau menjalankan program dengan semaksimal mungkin. Kendala eksternalnya adalah kesadaran wali murid akan program sekolah tersebut. Upaya yang dilakukan kepala MIN 1 dan MIN 2 Flores Timur sebagai manajer dalam meningkatkan mutu sekolah untuk mengatasi masalah internal dan eksternal adalah mengkomunikasikan kepada guru-guru untuk lebih aktif melakukan atau menjalankan program yang telah direncanakan.Kata kunci: Kepala Sekolah, Manajer, Studi Multisitus